2015
DOI: 10.1002/app.41823
|View full text |Cite
|
Sign up to set email alerts
|

Morphology, structure, and photovoltaic properties of poly(3‐hexylthiophene) and [6,6]‐phenyl‐C61‐butyric acid methyl ester‐based ternary blends doping with polystyrene of different tacticities

Abstract: The influence of the polystyrene of different tacticities on the morphology, phase structure, and photovoltaic properties of poly(3-hexylthiophene) (P3HT) and [6,6]-phenyl-C61-butyric acid methyl ester (PCBM) blend has been extensively investigated. The atactic polystyrene (aPS) immiscible with P3HT tended to form the phase-separated and columnar structure at low aPS weight ratio. Besides, the aPS could migrate to the surface of the films with PCBM phase distributing in the interfaces between P3HT and aPS doma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2016
2016
2017
2017

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 41 publications
0
3
0
Order By: Relevance
“…Data analysis is further complicated by the presence of other potentially unstable donors that can degrade alongside the PC 61 BM material of interest, which generates a need for a stable partner material in order to isolate the role of oxidation of PCBM from other components in the device. Several authors have noted that PC 61 BM and polystyrene (PS) are readily miscible [42,43] with the addition of PS aiding the formation of stable films, modification of crystal domains [44], simplification of processing [45], or even inclusion in devices to modify morphology [46]. Indeed, additions of PS to PC 61 BM films are being considered as an advantageous development in their own right for perovskite type solar cells, where the improved quality of the film results in open circuit voltage improvements to the finished device [47].…”
Section: Mmentioning
confidence: 99%
See 1 more Smart Citation
“…Data analysis is further complicated by the presence of other potentially unstable donors that can degrade alongside the PC 61 BM material of interest, which generates a need for a stable partner material in order to isolate the role of oxidation of PCBM from other components in the device. Several authors have noted that PC 61 BM and polystyrene (PS) are readily miscible [42,43] with the addition of PS aiding the formation of stable films, modification of crystal domains [44], simplification of processing [45], or even inclusion in devices to modify morphology [46]. Indeed, additions of PS to PC 61 BM films are being considered as an advantageous development in their own right for perovskite type solar cells, where the improved quality of the film results in open circuit voltage improvements to the finished device [47].…”
Section: Mmentioning
confidence: 99%
“…No O(1s) signal is observed at all for PS below the top surface with only a minor increase in O(1s) signal for PC 61 BM to 3.9 ± 0.5 At% below the top surface, which suggests that the PS-PC 61 BM blended film is less stable than either PS or PC 61 BM individually. Pristine PC 61 BM films have previously been observed to form aggregated clusters which shrink in size when blended with PS, and also that some PC 61 BM clusters are entrapped within polystyrene composites [42,46] which would provide additional interfaces that could be attacked. The extremely complex and extended interfaces formed between different domains in the polymer blends typically used in OPV devices offer a ready potential pathway for oxygen (and nitrogen) ingress into blended films that is not available to either pure material.…”
Section: Mmentioning
confidence: 99%
“…This structure provides high interfacial area for charge transport but lowers the crystallinity of PCBM. It has also been reported that addition of syndiotactic polystyrene can further enhance the efficiency by increasing the crystallization of P3HT 45 . BHJs prepared by grafting P3HT on to the surface of PCBM have shown to improve the thermal stability of the system and obtain domain sizes of around 5 nm.…”
mentioning
confidence: 95%